Thromboaspiration of a left-sided bioprosthetic valve thrombosis by a mini-access: the Lausanne novel procedure - Gunga, Ziyad; Rubimbura, Vladimir; Oberson, Denise; Monney, Pierre; Bechtold, Xavier; Ltaief, Zied; Rancati, Valentina; Eeckhout, Eric; Kirsch, Matthias (Frontiers in Cardiovascular Medicine, 2024)
Left-sided bioprosthesis valve thrombosis (LSBVT) is a challenging complication necessitating invasive interventions. We introduce a novel, minimally-invasive approach. We used a cerebral-embolic-protection-system and an Occlutech® cannula connected to an extracorporeal circuit, providing safer thrombus aspiration compared to the AngioVac-system. This technique offers a promising alternative for high-risk patients with LSBVT. Learning objectives 1. Understand the clinical challenges associated with left-sided bioprosthesis valve thrombosis (LSBVT), including its multifactorial causes and the limitations of traditional treatment options. 2. Introduce the Lausanne Procedure, a pioneering minimally-invasive approach for treating LSBVT, including its surgical technique and use of cerebral embolic protection systems ensuring neurological security. 3. Recognize the safety considerations and technical features of the procedure, including the use of the Occlutech® cannula as the aspirating cannula, as an alternative to the AngioVac-system. 4. Examine the potential advantages of the Lausanne Procedure, such as reduced complications, shorter hospital stays, and improved patient outcomes, in comparison to conventional interventions (redo-surgery)